Perioperative beta-adrenoblocker therapy and cardiovascular event risk: are all the problems solved? - Yu. M. Lopatin (Кардиоваскулярная терапия и профилактика, 2009)
The paper focuses on beta-blocker potential in perioperative period among the patients undergoing non-cardiac surgery. The results of two randomised clinical trials, POISE (2007) and DECREASE (1999-2009), are analysed.